Integralisme Islam dan Kontribusi Budaya Muakhi Bagi Peradaban Masyarakat Serta Relevansi Nilai-Nilai Filosofis Budaya Lokal dan Pembangunan Masyarakat Lampung - Nurdin, A. Fauzie (Universitas Islam Negeri Raden Intan Lampung, 2019)
This study reveals and explains about 'Islamic Integralism and the Contribution of Muakhi Culture to World Civilization, which is focused on the relevance of the philosophical values of Local Culture and Lampung Community Development'. The problems are: (1) Are Islamic values integrated with the philosophical values of the local culture as a philosophy of life for the people of Lampung ?; (2) How is the nature of Islamic values integrated with Lampung culture in relation to the life cycle of humans, nature and the environment; (3) How are the philosophical values of local culture (muakhi) relevant to the development of Lampung society. The research aims to uncover and explain the three problems scientifically, objectively, philosophically and academically. The philosophical approach is used to explain problems that must be